MEDIA PLAYFULL CREATIVE ALPHABET BOARD SEBAGAI SARANA PEMBELAJARAN UNTUK MENSTIMULASI KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN - R, Setyaning Wiwik; Yafie, Evania; Astuti, Wuri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Language is an important tool in building children's social skills and plays a role in all aspects of life, especially communication. The golden age is the development of language that requires stimulation through learning that is rich in fun language. The purpose of this research and development is to create a playful creative alphabet board "flash card" media for language skills in children aged 4-5 years. Educators need to provide advice, provide teaching media to create interesting learning so that it is not boring. The method used in this study is the Research and Development (R&D) method into five stages, namely analysis, design, development, implementation and evaluation. Playful Creative Alphabet Board media as an effective learning aid can improve children's language skills in understanding instructions, constructing simple sentences, and recognizing and pronouncing letters correctly. Media that has achieved the criteria very well to meet the results of the feasibility test of all material experts at the small group test level and feasibility aspects.